Anti-system politics : the crisis of market, liberalism in rich democracies - Hopkin, Jonathan 1967- (Oxford University Press, 2020)
Introduction : a quick history of the present -- Parties against markets : the rise and fall of democratic capitalism -- Explaining the rise of anti-system parties : inequality, debt and the crisis -- American nightmare : how neoliberalism broke US democracy -- Taking back control : Britain turns against the market -- The new North-South divide : bailout politics and the return of the left in Southern Europe -- Spain : boom, bust and break-up -- Basta! : anti-system politics in Italy -- Conclusions.